Use of antidepressants near delivery and risk of postpartum hemorrhage: cohort study of low income women in the United States - Palmsten, Kristin (BMJ Publishing Group Ltd., 2013)
Objective To determine whether use of serotonin or non-serotonin reuptake inhibitors near to delivery is associated with postpartum hemorrhage. Design Cohort study. Setting 2000-07 nationwide Medicaid data (Medicaid Analytic eXtract). Population 106 000 pregnant women aged 12-55 with a diagnosis of mood or anxiety disorder. Women were categorized into four mutually exclusive exposure groups according to pharmacy dispensing data: current (delivery date), recent (1-30 days before delivery date), past (1-5 months before delivery date), and no exposure (reference group). Main outcome measures Risk of postpartum hemorrhage by timing of exposure and by serotonin or non-serotonin reuptake inhibitors, classes of antidepressant, and antidepressant types. Relative risks and 95% confidence intervals adjusted for delivery year, risk factors for postpartum hemorrhage, indicators of severity of mood/anxiety disorder, other indications for antidepressants, and other drugs. High dimensional propensity score (hdPS) methods were used to empirically identify and adjust for additional factors. Results 12 710 (12%) women had current exposure to serotonin reuptake inhibitor monotherapy, and 1495 (1.4%) women had current exposure to non-serotonin reuptake inhibitor monotherapy. The risk of postpartum hemorrhage was 2.8% among women with mood/anxiety disorders but no exposure to antidepressants, 4.0% in the current users of serotonin reuptake inhibitors, 3.8% in the current users of non-serotonin reuptake inhibitors, 3.2% in the recent users of serotonin reuptake inhibitors, 3.1% in the recent users of non-serotonin reuptake inhibitors, 2.5% in the past users of serotonin reuptake inhibitors, and 3.4% in the past users of non-serotonin reuptake inhibitors. Compared with no exposure, women with current exposure to serotonin reuptake inhibitors had a 1.47-fold increased risk of postpartum hemorrhage (95% confidence interval 1.33 to 1.62) and women with current non-serotonin reuptake inhibitor exposure had a 1.39-fold increased risk (1.07 to 1.81). Results were similar with hdPS adjustment. Women with current exposure to serotonin reuptake inhibitors had an adjusted excess risk of 1.26% (0.90% to 1.62%), with a number needed to harm of 80, and for women with current exposure to non-serotonin reuptake inhibitors the excess risk was 1.03% (0.07% to 1.99%), with a number needed to harm of 97. For exposure to serotonin reuptake inhibitors the relative risk was 1.19 (1.03 to 1.38) for recent exposure and 0.93 (0.82 to 1.06) for past exposure; for non-serotonin reuptake inhibitors the figures were 1.17 (0.80 to 1.70) and 1.26 (1.00 to 1.59), respectively. Current exposure to selective serotonin reuptake inhibitor monotherapy was also associated with postpartum hemorrhage (1.42, 1.27 to 1.57), as was current serotonin norepinephrine (noradrenaline) reuptake inhibitor (1.90, 1.37 to 2.63) and tricyclic monotherapy (1.77, 0.90 to 3.47). All types of selective serotonin reuptake inhibitors available for analysis and venlafaxine, a serotonin norepinephrine reuptake inhibitor, were significantly associated with postpartum hemorrhage. Conclusions Exposure to serotonin and non-serotonin reuptake inhibitors, including selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, and tricyclics, close to the time of delivery was associated with a 1.4 to 1.9-fold increased risk for postpartum hemorrhage. While potential confounding by unmeasured factors cannot be ruled out, these findings suggest that patients treated with antidepressants during late pregnancy are more likely to experience postpartum hemorrhage.